Changes in The Sound and Exploration of The Depth of Its Meaning in Surah Al-Fath (Analysis of I'jaz Al-Qur'an) - Siti Humaira; Muhammad Anas (Universitas Islam Negeri Syarif Hidayatullah Jakarta, 2023)
This study aims to identify the forms of sound changes contained in Surat Al-Fath and their relevance to the context of the meaning contained therein. Descriptive qualitative method is used in this research. The two sources used as references are the Qur'an Surah Al-Fath as the primary source and books related to the research topic as secondary sources. The data collection technique is done by using Imam 'Ashim's qira'at history of Hafs as the main foundation, then looking for differences in readings in ten qira'ats related to sound changes through idgham and ibdal. The analysis was conducted to find the relationship between the sound changes and the meaning in accordance with the context in Surah al-Fath. The results show that there are sound variations based on the readings of the ten qira'at imams, such as the fusion of two letters that meet or the replacement of harakat and letters in a reading. In addition to being intended to facilitate pronunciation, these sound changes contain explicit meanings that can be explored by looking at the context of the verse that includes them, although the original meaning of a word does not change. The depth of meaning indicated by these sound changes does not indicate a contradiction between one meaning and another, thus emphasizing the miracle of the Qur'an that every smallest sound arrangement is very relevant to the context of the meaning and intention to be conveyed.